SIMULATION AND MODELING OF MICROORGANISMS IN BIOFILM - Bissembayeva, Gulzhahan (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Biofilms are microstructured microbial communities that form at interfacies. In biofilms, microbial cells are encased in a matrix comprising polysaccharides, proteins, and extracelluar DNA. In the environment, biofilms contribute to biogeochemical cycles and pollutant degradation. However, biofilms are also responsible for more than 60% of infections and 80% of chronic infections [1, 2]. The phenotype of microorganisms in the biofilm is different compared to those in the planktonic state. Bacteria in biofilms have increased resistance to antibiotics, faster mutation accumulation rate, and higher virulence [3-10]. Biofilm are heterogenous and dynamic systems, in which biomass self-organize in response to nutrient availability, flow conditions, etc. While numerous techniques exist for biofilm growth and analysis, biofilm modeling allows simulating a broad range of growth conditions and provide preliminary information that reduce the number of experiments. Among others, agent-based models (ABM) have been used to simulate biofilm formation and growth. In these models, cells are described as individual automata that follow a simple set of rules (rules of life) to interact between each other and with the surrounding environment. While ABMs can be coded in any language, they are easy to implement in NetLogo, a simplified multi-agent programmable environment for modelling designed specifically for ABMs. In this thesis, the bacterial attachment, growth and biofilm propagation were modeled using the NetLogo. The model was run using parameters extracted from previous literature. This work provides a simple framework to test biofilm formation, propagation and dispersal in capillaries and other simple biomedical devices.
Keywords: DNA; biofilm; pseudomonas aeruginosa; PA; Research Subject Categories::TECHNOLOGY; agent-based model; ABM; Type of access: Embargo